2016
DOI: 10.3892/ijo.2016.3410
|View full text |Cite
|
Sign up to set email alerts
|

The pro-social neurohormone oxytocin reverses the actions of the stress hormone cortisol in human ovarian carcinoma cells in vitro

Abstract: The journey patients with ovarian cancer travel from non-specific symptoms causing delayed diagnosis through surgery and chemotherapy, culminating in a 5-year survival rate of 43%, must have a profound and detrimental psychological impact on patients. Emerging studies link higher levels of oxytocin (OT) and increased social support, an independent prognostic factor in cancer, with a moderating effect on stress. In contrast, there is a known association of tumour cell proliferation with elevated cortisol (stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 54 publications
0
19
0
1
Order By: Relevance
“…This team of investigators, therefore, proposed that a system involving P-LAP and oxytocin plays a role in the regulation of human endometrial adenocarcinoma, in which P-LAP exerts a functionally positive impact on carcinoma cell growth by degrading suppressive peptides such as oxytocin. More recently, these effects have also been linked with a cross-talk network between oxytocin and the stress hormone cortisol, whereby oxytocin reversed the carcinogenic effects of cortisol via autophagy (cellular self-degradation)[ 71 ]. Interestingly, pertinent to the postulated connection between oxytocin and symptoms of autism[ 39 ], oxytocin and cancer have also demonstrated an inverse relationship in autistic children[ 72 ].…”
Section: Oxytocin In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…This team of investigators, therefore, proposed that a system involving P-LAP and oxytocin plays a role in the regulation of human endometrial adenocarcinoma, in which P-LAP exerts a functionally positive impact on carcinoma cell growth by degrading suppressive peptides such as oxytocin. More recently, these effects have also been linked with a cross-talk network between oxytocin and the stress hormone cortisol, whereby oxytocin reversed the carcinogenic effects of cortisol via autophagy (cellular self-degradation)[ 71 ]. Interestingly, pertinent to the postulated connection between oxytocin and symptoms of autism[ 39 ], oxytocin and cancer have also demonstrated an inverse relationship in autistic children[ 72 ].…”
Section: Oxytocin In Cancermentioning
confidence: 99%
“…For example, instead of being increased as a direct response to exercise, oxytocin may be induced to assist its “companion” hormone, vasopressin, a well-known hormonal regulator of body fluid homeostasis[ 97 ]. Cortisol, the “stress hormone” and the rhythm surrounding its release has been linked to the progression and survival from various cancers[ 98 - 101 ], and has also been linked to oxytocin[ 71 , 72 ]. The ability to completely elucidate various pathways and mechanisms of actions would go a long way to showing if the established connection between the different hormones extends to cancer.…”
Section: Oxytocin In Cancermentioning
confidence: 99%
“…Therefore, we speculate that the activation of OXTRs inhibits the progression of ovarian cancer. Although OXT inhibited the proliferation, migration and invasion of ovarian cancer as reported 8 , 9 , its underlying mechanisms had not fully elucidated. Morita et al found that OXT inhibited the proliferation, migration and invasion of ovarian cancer by enhancing the expression of E-cadherin and slightly inhibiting MMP-2 in cultured SKOV3 cells 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Morita et al found that OXT inhibited the proliferation, migration and invasion of ovarian cancer by enhancing the expression of E-cadherin and slightly inhibiting MMP-2 in cultured SKOV3 cells 8 . Mankarious et al revealed that OXT induced apoptosis in cultured three ovarian cancer cell lines including SKOV3, MDAH-2774 and PEO1 9 . Here we first reported that OXT suppressed the ovarian cancer metastasis by repressing not only the expression of MMP-2, but also angiogenesis in cultured A2780 cells.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 A secreção crônica de cortisol, em resposta a eventos estressores, tem sido associada com o desenvolvimento de patologias diversas como: doença cardíaca coronoriana, 4 osteoporose, 8 úlcera de membros inferiores 9 e recentemente há um crescente número de estudos que apontam uma correlação positiva entre aumentos crônicos dos níveis plasmáticos de cortisol induzido por estresse e desenvolvimento de neoplasias. [10][11][12][13] Tentativas de associar a etiologia das neoplasias malignas com os eventos estressantes diários datam desde a Grécia antiga, onde Galeno sugeria que mulheres melancólicas e depressivas eram mais propensas a desenvolver o câncer do que aquelas com um alto astral. 6 Embora até então muitos estudos tenham sido realizados neste âmbito, ainda não há um consenso quanto à influência dos eventos estressores diários no desenvolvimento de neoplasias.…”
Section: Introductionunclassified